PELAKSANAAN PENILAIAN DALAM PEMERIKSAAN PENGUJIAN KEPATUHAN WAJIB PAJAK: (Studi pada Kantor Pelayanan Pajak Madya Bekasi) - Masda Surya Wicaksana; Ferry Irawan (Media Mahardhika, 2021)
This research aims to review the appraisal process in the compliance of taxpayers' audits at the Bekasi Medium Tax Office (MTO) and identify the constraints that arise in the field during the appraisal process. The research was carried out by raising taxpayers' audits to test the fairness of land transfer value conducted by PT XYZ in 2017. The business review was carried out by conducting recalculation practices on case studies at MTO Bekasi with guidance and tax appraisal direction. The practice of recounting is carried out to maintain the data's confidentiality from the MTO Bekasi report. Also, reviews are carried out by comparing existing regulations with existing activities in the field.